2005
DOI: 10.1002/ijc.21137
|View full text |Cite
|
Sign up to set email alerts
|

Green tea drinking and multigenetic index on the risk of stomach cancer in a Chinese population

Abstract: The purpose of our study was to examine the roles of green tea drinking, other risk and protective factors, and polymorphism of susceptibility genes such as GSTM1, GSTT1, GSTP1, and p53 codon 72 and their possible joint effects on the risk of stomach cancer. A population-based case-control study was conducted in Taixing, China, including 206 newly diagnosed cases with stomach cancer and 415 healthy control subjects. Epidemiological data were collected by in-person interviews using a standard questionnaire. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 63 publications
1
114
1
Order By: Relevance
“…31 Mu et al reported a more than multiplicative interaction between green tea drinking and alcohol drinking (OR 5 4.57; 95% CI 5 1.62-12.89) in a study on stomach cancer. 32 However, smoking and alcohol drinking were not observed as significant effect modifiers to tea drinking in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…31 Mu et al reported a more than multiplicative interaction between green tea drinking and alcohol drinking (OR 5 4.57; 95% CI 5 1.62-12.89) in a study on stomach cancer. 32 However, smoking and alcohol drinking were not observed as significant effect modifiers to tea drinking in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…33 The study was restricted to individuals who lived in Taixing for at least 10 or more years. Eligible patients were those who were diagnosed with ESCC from June 1, 2000 to December 30, 2000 with pathologically or clinically confirmed diagnoses reported to the Taixing Tumor Registry.…”
Section: Participantsmentioning
confidence: 99%
“…Additional catechins found in green tea include (−)-epicatechin (EC), (−)-epigallocatechin (EGC), and (−)-epicatechin-3-gallate (ECG). Epidemiologic studies have revealed a reduction in colon cancer incidence in individuals that consumed tea (5), an inverse correlation between urinary tea polyphenols and gastric cancer (6), and an improved prognosis of stage I and II breast cancer patients in those patients that drank five or more cups of green tea (7). More recently, a meta-analysis suggested a modest effect on lung cancer risk (8).…”
mentioning
confidence: 99%
“…6 The HGF/c-Met pathway is deregulated in numerous types of malignancies, including breast, prostate, and gastric cancers (14). In prostate cancer, the transmembrane receptor c-Met is often overexpressed in primary tumors and metastases.…”
mentioning
confidence: 99%